Recovery Potential After Acute Stroke - Seitz, Rüdiger J.; Donnan, Geoffrey A. (Frontiers in Neurology, 2015)
In acute stroke the major factor for recovery is the early use of thrombolysis aimed at arterial recanalization and reperfusion of ischemic brain tissue. Subsequently, neurorehabilitative training critically improves clinical recovery due to augmention of postlesional plasticity in acute stroke. Neuroimaging and electrophysiology studies have revealed that the location and volume of the stroke lesion, the affection of nerve fibre tracts as well as functional and structural changes in the perilesional tissue and in large-scale bihemispheric networks are relevant biomarkers of post-stroke recovery. However, associated disorders such as mood disorders, epilepsy and neurodegenerative diseases may induce secondary cerebral changes or aggravate the functional deficits and, thereby, compromise the potential for recovery.